2021
DOI: 10.1007/s11678-021-00658-5
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoparalysis and pseudoparesis of the shoulder

Abstract: Background Clinical presentation of massive rotator cuff tears range from pain to loss of active range of motion. Pseudoparalysis and pseudoparesis are defined inconsistently in the literature, but both include limited active with maintained passive range of motion. Objective This article aims to provide a consistent definition of pseudoparalysis and pseudoparesis of the shoulder and show structural and biomechanical differences between these two types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…The terms pseudoparesis and pseudoparalysis are used interchangeably and inconsistently in the literature related to MIRCT [ 8 , 9 , 35 ]. Some authors define pseudoparalysis as a massive rotator cuff tear that leads to a limited active forward flexion of less than or equal to 45° without passive restriction or neurological deficit, and that pseudoparesis differs only by having limited active forward flexion of greater than 45° and less than or equal to 90° [ 35 ].…”
Section: Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The terms pseudoparesis and pseudoparalysis are used interchangeably and inconsistently in the literature related to MIRCT [ 8 , 9 , 35 ]. Some authors define pseudoparalysis as a massive rotator cuff tear that leads to a limited active forward flexion of less than or equal to 45° without passive restriction or neurological deficit, and that pseudoparesis differs only by having limited active forward flexion of greater than 45° and less than or equal to 90° [ 35 ].…”
Section: Definitionsmentioning
confidence: 99%
“…These authors attempted to gain clarity on the terminology by defining pseudoparalysis as a massive rotator cuff tear with 0° of active elevation and full passive elevation, and pseudoparesis as a massive rotator cuff tear with less than 90° active elevation and full passive elevation. The lack of agreement on terminology was highlighted in another systematic review which identified that of the 16 studies included, four did not differentiate between pseudoparalysis and pseudoparesis, five studies did not define either, and seven studies had heterogenous definitions [ 8 ]. This lack of consensus is further highlighted by a survey of 246 shoulder surgeons which demonstrated a lack of agreement on how best to define pseudoparalysis, and low inter-rater agreement when assessing via a video consultation [ 36 ].…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…gehören zu den häufigsten muskuloskeletalen Erkrankungen und können mit ausgeprägten Schmerzen und Funktionseinschränkungen -im Extremfall auch völligem Funktionsverlust der oberen Extremitäteinhergehen [10,61]. Die Prävalenz in der allgemeinen Bevölkerung ist besonders vom Alter, aber auch von Faktoren wie Händigkeit und Belastungsprofil abhängig und liegt zwischen 10 % in der jungen Erwachsenenbevölkerung und über 60 % in der Generation der über 80-Jährigen [49,75,82].…”
Section: Rotatorenmanschettenrupturenunclassified